PENGARUH LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Wahyu Dhermawan, Rizky; Terawati, Mira Teram; Suryati, Elis (Publika Citra Media, 2024)
Financial Statement is an important source of information used in decision making related to the future of the company. Leverage is one of the important factors that will affect the company's financial performance in terms of achieving profitability because it can increase the company's capital with the aim of increasing profits. This study aims to determine the effect of levergae ratio on the financial performance of property and real estate companies listed on the Indonesia Stock Exchange (IDX). The technique of determining the companies that were sampled in this study used purposive sampling and produced 35 companies. The method in this study is descriptive verifiative. The data in this study used secondary data from the IDX. The analysis used is liner regression. The results showed that leverage affected financial performance by 41.1%.